2020
DOI: 10.1038/s41415-020-1713-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: establishing an oral surgery-led urgent dental care hub

Abstract: Addresses the evolving advice and guidance from leading government dental bodies affecting the profession. Provides a working example for setting up and developing an urgent dental care centre. Discusses the current and future challenges likely to face the profession amid this international crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…8,9,10,11,24,27,28 Anxiety and distress over rapidly changing guidelines and PPE availability can have a tangible impact on efforts to maintain a sustainable workforce. 9 The overwhelming demand and reduced capacity provided by UDC services, which is in line with previously reportedly UDC service evaluation data, 14,15 was highlighted by the majority of our participants and further heightened the stressfulness of UDC environments. Feeling undervalued, fuelled by a lack of communication from governing bodies, was unanimously stated and echoes feelings of 'institutional betrayal' expressed by the dental profession as reported by Collin et al 29 Lack of understanding and support at national level and from senior management may have driven enhanced teamwork at a clinic level, as clinicians developed their own support systems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…8,9,10,11,24,27,28 Anxiety and distress over rapidly changing guidelines and PPE availability can have a tangible impact on efforts to maintain a sustainable workforce. 9 The overwhelming demand and reduced capacity provided by UDC services, which is in line with previously reportedly UDC service evaluation data, 14,15 was highlighted by the majority of our participants and further heightened the stressfulness of UDC environments. Feeling undervalued, fuelled by a lack of communication from governing bodies, was unanimously stated and echoes feelings of 'institutional betrayal' expressed by the dental profession as reported by Collin et al 29 Lack of understanding and support at national level and from senior management may have driven enhanced teamwork at a clinic level, as clinicians developed their own support systems.…”
Section: Discussionsupporting
confidence: 87%
“…These studies have focused on processes implemented to operationalise UDCs and on their clinical activity and output. 13,14,15 To date, no published study has explored and reported frontline experiences of what it was actually like to work within a UDC and why. This is surprising considering the long-term impact of COVID-19 and UDC operations on dentistry, the richness of lessons potentially learnt from this time and the high likelihood that processes, such as the ones used during COVID-19, will be required in the future again.…”
Section: Introductionmentioning
confidence: 99%
“…Soylu ve arkadaşları 25 çalışmamıza benzer şekilde pandemi döneminde son 2 yıla kıyasla hasta sayısının % 90 oranında azaldığını rapor etmişlerdir. Shah ve arkadaşları 35 ise hastalara telefonla triaj yaptıktan sonra sadece acil durumlarda hastaneye başvurulmasını istemişlerdir. Hastaneye başvuran hastaların ise % 67'sinin oral cerrahi kliniğinde tedavi gördüğü belirtilmiştir.…”
Section: Sonuçunclassified
“…Prior to implementing the modified treatment pathway 39 for patients attending for emergency dental extraction, the telephone number to access the Acute Dental Care service was already publicly available via the hospital trust website. During the time period for which these data were collected, attending dentists, oral surgeons and dental nurses were anecdotally informed by a number of patients that this telephone number was circulated via social media and by GDPs at the height of the first wave of the pandemic.…”
Section: Antibiotic Prescription In Exceptional Circumstancesmentioning
confidence: 99%